A Psycholinguistic Approach in Prenatal Care: The Effectiveness of Madurese-Language EFT Videos in Reducing Maternal Anxiety - Suwarni, Linda; Ningsih, Sri Wahyu; Selviana, Selviana (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2026)
Unhealthy prenatal anxiety carries the risk of triggering complications for the mother and fetus, such as Low Birth Weight (LBW). This study aims to analyze the effectiveness of the Emotional Freedom Technique (EFT) video in Madurese on the anxiety levels, knowledge, and attitudes of pregnant women. Using a pre-experimental design (one group pretest-posttest), this study involved 32 respondents in Sungai Malaya Village, Kubu Raya Regency, selected through purposive sampling. The intervention was a 5-minute 59-second educational video that integrated modern psychology, acupressure, and a local language approach. Wilcoxon Signed Rank Test analysis showed a significant increase in knowledge (p=0.048) and attitudes (p=0.001), while anxiety scores decreased substantially from 29.72 to 24.50 (p=0.001). Psycholinguistically, the use of the mother tongue has been shown to reduce cognitive barriers and build emotional closeness, making educational messages more easily accepted through imagination. The tangible impact after the intervention showed changes in maternal behavior, becoming calmer and more adaptive in managing daily stress, as well as a shift from a passive to a more proactive attitude towards mental health prevention efforts. This study contributes to public health strategies in creating inclusive and culturally based intervention models. In conclusion, the local language-based EFT intervention was effective in triggering changes in preventive behavior and reducing anxiety levels in pregnant women clinically, while also serving as a reference for health promotion programs in rural areas with ethnic diversity.